Shifting (but not Crossing) Human and Animal Boundaries in the COVID-19 Era - Kantha, Pana (Journal of Social Sciences Naresuan University, 2020)
The wildlife’s appearance during lockdown to prevent the COVID-19 era is presented as boundary-shifting between humans and animals. The human-animal boundary is based on the Western naturalistic ontology. However, this article found that the spectacular news of the wildlife’s appearance during the COVID-19 era are still based on the anthropocentric view, especially through the rigid scientific thinking on conservation of nature and wildlife. Moreover, although the journalists tended to present the appearance of animals as a boundary-shifting between humans and animals, this article found that these representations as such are merely shifting but not crossing the existing boundaries. In addition, such representations intensify the naturalistic boundary between humans and animals and between culture and nature. By presenting the animal appearance under naturalistic ontology, they help strengthening of the dividing-line between humans and animals, and also reinforces the notion that humans have a higher status above animals according to hierarchy of the natural world. The more animals appear closer to the state of nature, the greater the human becomes spectacularly affected by their appearance. This brings about the human construction of the nature which is merely a part of human culture.